2010
DOI: 10.1007/s10800-010-0107-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of TiO2 layers deposited on YSZ on the electrochemical promotion of C2H4 oxidation on Pt

Abstract: The electrochemical promotion of Pt/YSZ and Pt/TiO 2 /YSZ catalyst-electrodes has been investigated for the model reaction of C 2 H 4 oxidation in an atmospheric pressure single chamber reactor, under oxygen excess between 280 and 375°C. It has been found that the presence of a dispersed TiO 2 thin layer between the catalyst electrode and the solid electrolyte (YSZ), results in a significant increase of the magnitude of the electrochemical promotion of catalysis (EPOC) effect. The rate enhancement ratio upon c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…More recently, the effect of a TiO 2 interlayer was examined by Papaioannou et al 354 on the catalytic activity and EPOC behavior of C 2 H 4 oxidation on Pt by comparing a Pt/YSZ catalyst electrode and a Pt/TiO 2 /YSZ catalyst electrode under similar operating conditions in O 2 excess. It has been found that the presence of the dispersed TiO 2 interlayer results in a very significant increase in the magnitude of the electrochemical promotion effect upon anodic polarizations.…”
Section: Polymeric Proton Conductivementioning
confidence: 99%
“…More recently, the effect of a TiO 2 interlayer was examined by Papaioannou et al 354 on the catalytic activity and EPOC behavior of C 2 H 4 oxidation on Pt by comparing a Pt/YSZ catalyst electrode and a Pt/TiO 2 /YSZ catalyst electrode under similar operating conditions in O 2 excess. It has been found that the presence of the dispersed TiO 2 interlayer results in a very significant increase in the magnitude of the electrochemical promotion effect upon anodic polarizations.…”
Section: Polymeric Proton Conductivementioning
confidence: 99%
“…Herein, we rely on the model reaction of ethylene oxidation 31,32,[34][35][36][47][48][49][50] to demonstrate, using ab-initio computations, the effect of electrochemical potential on the surface reactivity. We will elucidate on the one hand the impact of the electrochemical potential on the surface state compared to thermal catalysis and on the other hand, the impact of the potential generated electric field on the reactivity of ethylene and oxygen activation.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, EPOC studies have been performed over continuous-film catalysts 4,5 ; however, recent studies have been implementing the use of nanocatalysts by supporting them on MIEC material 6 (i.e., CeO 2 7 and TiO 2 8 ). The use of nanoparticles allows for the reduction in the amount of noble metal required as a catalyst 9,10 .…”
Section: Introductionmentioning
confidence: 99%